Health needs of people with pulmonary tuberculosis - Aliéren Honório Oliveira; Antonio Germane Alves Pinto; Glauberto da Silva Quirino; Rachel de Sá Barreto Luna Callou Cruz; Maria Lúcia Duarte Pereira; Edilma Gomes Rocha Cavalcante (Universidade Federal de Santa Maria, 2021)
Objective: to analyze the health needs of people undergoing treatment for tuberculosis assisted by health services. Method: a descriptive study with a qualitative approach, carried out with ten patients assisted by the Family Health Strategy teams and a reference service. The interviews were submitted to the thematic analysis technique and analyzed according to the Operational Taxonomy of Health Needs. Results: the patients reported needs for food and housing, were satisfied with the treatment, accessibility and cordiality of the health professionals, but dissatisfied with the investigation symptoms and evolution of the clinical picture. The bond with the nurse was positive. Orientations and search for information subsidized the autonomy and the way of living life. Conclusion: patients recognized the health needs related to access to technologies that improve and prolong life, but require precise diagnostic investigation, guidance for autonomy and ordering Primary Health Care.